Pemberdayaan Ekonomi Ummat Berbasis Perbibitan Sapi Bali Bersama Majelis Ulama Indonesia Nusa Tenggara Barat - Hailuddin; Tamzil, Mohammad Hasil (Jurnal Pengabdian Magister Pendidikan IPA, 2024)
This community service activity was carried out with the aim of creating jobs for underprivileged communities in Beririjarak village, Wanasaba District, East Lombok. This activity was held in collaboration with the University of Mataram with the Indonesian Ulema Council of West Nusa Tenggara (MUI-NTB) with the Barokah Farmer Group of Beririjarak village. MUI acts as a provider of funds, while the Barokah farmer group acts as a beneficiary, while the team from Mataram University acted as technical and business advisors. The activity began with focus group discussion (FGD), group formation and program preparation. The results of the FGD were stated in the form of a letter of understanding signed jointly by the chairman of MUI-NTB with the Chairman of the Barokah Beririjarak Farmer Group, and witnessed by several MUI-NTB employees, located at the MUI-NTB office, Pejanggik street Mataram. In the meeting, a livestock handover ceremony was also held by the chairman of MUI-NTB to the head of the Barokah farmer group, Beririjarak village, East Lombok. The purchase of livestock is carried out using two methods, namely direct purchases made by MUI-NTB officials. The second method is that the purchase of livestock is handed over to thefarmer, and if they can buy it at a lower price than the agreed benchmark price, the excess money can be used to pay for the repair of cages and other production facilities. The first evaluation result at the Barokah Farmer Group's business location was to stand a simple pen unit filled with 10 heifers, with 4 of them pregnant. In this way, the purpose of activities to create jobs for underprivileged communities can be achieved.